Circulating tumor cell detection using a parallel flow micro-aperture chip system1. Issue 7 (7th April 2015) - Chang, Chun-Li; Huang, Wanfeng; Jalal, Shadia I.; Chan, Bin-Da; Mahmood, Aamer; Shahda, Safi; O'Neil, Bert H.; Matei, Daniela E.; Savran, Cagri A.
<x xml:space="preserve">Abstract</x> A parallel flow micro-aperture chip system for detection of circulating tumor cells.